KESALAHAN BERBAHASA SISWA SEKOLAH DASAR DI KABUPATEN LAMONGAN - Ghufron, Syamsul (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This study aims to uncover language errors (spelling mistakes, word choice errors, sentence errors) elementary school students in Lamongan District. To achieve these objectives qualitative research is conducted with the steps: to collect data on the students’ language errors and to analyze the error language. The subjects of the study were elementary school students in Lamongan District. In the data collection techniques used tests, techniques refer, and record techniques. The result of the research indicates the existence of errors in the language of the students’ writing covering spelling errors (basic writing errors, capital use errors, prefixing errors, preposition writing errors, abbreviations, and punctuation errors) words of speech), and the error of composing sentences (incomplete sentences, not frugal sentences, and sentences containing interference).